Controllable distribution of reinforcements for reducing the strain energy in dissimilar ceramic/metal joints. Issue 2 (February 2021) - Feng, Qinghua; Lin, Panpan; Lin, Tiesong; He, Peng; Liu, Yan; Long, Weimin; Li, Jian
Highlights: SiC Reinforcements are controlled to cluster together in the center of joint domain. Controllable spatial distribution of SiC realizes multi-layer architecture of joint. For ceramic/metal joint, multi-layer architecture relaxes strain energy in ceramic. For ceramic/metal joint, drop of strain energy in ceramic increases shear strength. Abstract: A novel design of a multi-layered joint architecture, characterized by the controllable spatial distribution of ceramic reinforcements, was obtained, when brazing ZrB2 -SiC ceramics and Ti-6Al-4 V reinforced by TiB whiskers with AgCu filler. To induce SiC reinforcements to cluster together, within the center of the filler and especially away from the ZrB2 -SiC, SiC was added into joint, in the form of a SiC interlayer featuring a 3D-bridged network structure with continuous micro-channels infiltrated by capillary force by liquid filler during brazing. Different SiC particles were connected together, by micro-bridges being not destroyed during brazing. The layer rich in SiC could reduce thermal expansion mismatch between different substrates, the AgCu next to the ZrB2 -SiC could relax the strain energy by high plastic deformation. Compared to joint brazed with single AgCu, joint strain energy decreased from 10.8 × 10 −6 J to 8.6 × 10 −6 J, accordingly joint shear strength increased from ∼5.4 MPa to ∼41.2 MPa.